2012
DOI: 10.1021/bk-2012-1094.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Many-Body Nodal Hypersurface and Domain Averages for Correlated Wave Functions

Abstract: We outline the basic notions of nodal hypersurface and domain averages for antisymmetric wave functions. We illustrate their properties and analyze the results for a few electron explicitly solvable cases and discuss possible further developments.PACS numbers: 61.46.+w, 36.40.Cg Quantum Monte Carlo is one of the most effective many-body methodologies for the study of quantum systems. It is based on a combination of analytical insights, robustness of stochastic approaches, and performance of parallel archite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…After introducing the nodal domain averages [17], we later found that the nda expressions correspond to a special case of identity which was derived idependently by Sogge and Zelditch [28]. We will present here the identity in a form that includes potentials which is a straightforward generalization (the original paper [28] assumes Laplacian eigenstates, i.e., with no potentials).…”
Section: Weighted Nodal Domain Averagesmentioning
confidence: 91%
See 4 more Smart Citations
“…After introducing the nodal domain averages [17], we later found that the nda expressions correspond to a special case of identity which was derived idependently by Sogge and Zelditch [28]. We will present here the identity in a form that includes potentials which is a straightforward generalization (the original paper [28] assumes Laplacian eigenstates, i.e., with no potentials).…”
Section: Weighted Nodal Domain Averagesmentioning
confidence: 91%
“…i) The nda components differ for degenerate eigenstates. For example, building upon previous work [17], we were able to analytically derive that for the noninteracting Be atom ground and excited state the components show clearly different values (in previous work the values for the state 1 S (1s 2 2p 2 ) were estimated numerically). These values are shown in Table 1.…”
Section: Nodal Domain Averagesmentioning
confidence: 94%
See 3 more Smart Citations